IKAN PETEK (Leiognathus sp.) DALAM PEREKONOMIAN NELAYAN SURADADI KABUPATEN TEGAL - Hendrayana Hendrayana; Intan Herwindra Millyaningrum; Ninik Umi Hartanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Ponyfishes (Leiognathus sp.) is  classified as economic fish in Tegal. Thisaims of this research was to economic value Ponyfishes (Leiognathus sp.) forSurodadi fisherman, Tegal. The descriptive method was applied in research.Data analysis used to fish catch analysis, ponyfishes production andPonyfishes utilization by fishermen. The highest Surodadi fisheriesproductivity in July. Surodadi's fishery productivity declined one of them isPonyfishes. Ponyfishes used to salted fish and animal feed. Science andtechnology needed to economy increase Surodadi fisherman  Keyword : Ponyfishes, Leiognathus sp. ,  Sal t ed Fi sh,  fisherman, Tegal